Promising practices for fathers' involvement in children's education - Ho, Hsiu-Zu; Hiatt-Michael, Diana B. (Family, school, community, partnership issues., 2012)
A timely collection of sound research addresses father involvement in their children's education. Promising Practices for Fathers' Involvement in Their Children's Education visits a less known side of parent involvement, the side of fathers' active engagement with their children's education in the home and that is less visible in the schools. Their contributions from preschool to career decision-making and accessibility to their children's education are covered in ten chapters, focusing on in-depth research from Canada to Argentina and Korea to Africa.